Single-channel analysis of inactivation-defective rat skeletal muscle sodium channels containing the F1304Q mutation. - Lawrence, J H (1996)
The intracellular linker between domains III and IV of the voltage-gated Na channel mediates fast inactivation. Targeted alteration of one or more of a triplet of hydrophobic amino acids within this linker region results in a marked slowing in the decay of ionic current. The mechanism of this defective inactivation was explored in rat skeletal muscle sodium channels (mu 1) containing the F1304Q mutation in Xenopus laevis oocytes with and without coexpression of the rat brain beta 1 subunit. Cell-attached single-channel patch-clamp recordings revealed that the mu 1-F1304Q channel reopens multiple times with open times that are prolonged compared with those of the wild-type channel. Coexpression of the beta 1 subunit stabilized a dominant nonbursting gating mode and accelerated the activation kinetics of mu 1-F1304Q but did not modify mean open time or fast-inactivation kinetics. A Markov gating model incorporating separate fast- and slow-inactivation particles reproduced the results by assuming that the F1304Q mutation specifically influences transitions to and from fast-inactivated states. These effects are independent of interactions of the mutant channel with the beta 1 subunit and do not result from a change in modal gating behavior. These results indicate that F1304Q mutant channels can still enter the inactivated state but do so reversibly and with altered kinetics.